Low carbon capability behavior framework as climate change mitigation for urban residential area in Putrajaya, Malaysia - Abas, Ani Shazwani (2017)
Malaysia’s rapid urbanization rate has led the country to contribute relatively high greenhouse gas emissions among the Southeast Asian countries. The carbon dioxide emission from the residential sector is expected to increase by the year 2020, with the emission factor based on residential energy consumption. The carbon dioxide (CO2), which is well-known as the most prevalent greenhouse gasses that cause global climate change, is scientifically proven are contributed by various human activities, especially in cities. Henceforth, the role of urban residents towards climate change mitigation effort is undoubtedly necessary. Many policies and plans have been developed in Malaysia towards mitigating climate change, including the Low Carbon Cities Framework and Assessment System (LCCF). Unfortunately, there is less focus has been paid to urban residents’ low carbon capability behavior in realizing the existing low carbon policies. This denotes that there is a gap between the policies and built plans with the urban resident’s low carbon capability behavior. Nevertheless, to promote the low carbon capability behavior, understanding urban resident’s climate change awareness is also crucial. Hence, an explanatory research was carried out to explore and propose the Low Carbon Capability Behavior Framework (LCCBF) for the urban residential area as a climate mitigation effort. Putrajaya, one of Malaysia federal territory, has been designed as the garden city, further has remarkably progressed its mission towards green and sustainable cities by the year 2025. Thus, it is selected as the sample population to carry out the research. The expert panel focus group discussion and urban residents survey for the Putrajaya case study was carried out to accomplish the research goal. The expert focus group discussions verified that the LCCBF should consist the main three aspects which are: the low carbon mobility, the low carbon living and housing, and the low carbon community choices. Meanwhile, urban resident’s behavior preferences and technology to support low carbon capability behavior is essential under each of the aspects. Whereas, the result of the survey revealed that the highly influencing factors towards urban residents low carbon capability behavior is the value of perceptions. The most preferred low carbon capability behavior was also highlighted and further proposed to be an indicator for the overall of the LCCBF. This study in additional, will guide local authorities to better understand the urban resident’s low carbon capability behavior, and improve their current program and plans towards promoting and implementing low carbon community. Meanwhile, town planners and designers, can enhance their knowledge in planning and designing the low carbon facilities for urban residential area that will encourage low carbon capability behavior.